Bridging the information gap: How digitalization shapes stock price informativeness - Li, Weiping; Li, Tingyu; Jiang, Dequan; Zhang, Xuezhi (Journal of Financial Stability, 2024)
Digitalization is a crucial strategy for firms to gain a competitive advantage. This study utilizes data from Chinese listed firms from 2011 to 2020 to examine how digitalization affects firms' stock price informativeness. Empirical results demonstrate that digitalization reduces stock price synchronicity and promotes firms' stock price informativeness. Moreover, digitalization improves stock price informativeness by enhancing investment efficiency and firm value, reducing information asymmetry, and alleviating agency costs. These findings suggest that effective digital strategies and capabilities constitute an important yet underappreciated resource that enables firms to generate value-relevant information and improve the information environment in emerging capital markets. Our study contributes new evidence on the financial market implications of digital transformation from a resource-based view perspective.